Canopy on Stair Tower' (1927)
Large drawing with description in writing and the bottom of the drawing. It reads "F.S.D. Canopy on stair cover (M.B) for Mr. W. R. Hearst, San Simeon, Julia Morgan Architecture." The drawing itself is a pillar with a woman reading a book, below her is an engraved platform. There are flowers engraved above her head. On the top is 3 pillars holding up center piece.